Helicobacter pylori infection increases the risk of thyroid nodules in adults of Northwest China - Di, Jia; Ge, Zhuang; Xie, Qingwei; Kong, Danfeng; Liu, Sha; Wang, Pengwei; Li, Jie; Ning, Ning; Qu, Wei; Guo, Rong; Chang, Danyan; Zhang, Jun; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Thyroid nodules (TNs) are very common in the adults of Northwest China. The role of Helicobacter pylori (H. pylori) infection in TNs is poorly investigated and even with controversial conclusions. Our study aimed at highlighting the relationship between H. pylori infection and the risk of TNs. Methods: 9,042 individuals were enrolled with thyroid ultrasonography and 14C-urea breath test (14C-UBT). Baseline characteristics and relevant covariates were obtained, including anthropometry and laboratory indicators. After applying the exclusion criteria, 8,839 patients were included and divided into 2 groups: a cross-sectional study of single follow-up (n=8,711) and a retrospective cohort study of multiple follow-ups for 5 years (n=139). Results: The prevalence of H. pylori infection and TNs was 39.58% and 47.94% in the adults of Northwest China, respectively. The prevalence of TNs was significantly higher among H. pylori-positive individuals than those without infection (52.55% vs. 44.92%, p＜0.01). The result of binary logistic regression revealed that the crude odds ratio (OR) was 1.624 (95% CI 1.242 2.123) in Model 1 without adjustment compared to H. pylori-negative group, and was also positive in Model 2, 3, and 4 (Model 2: OR=1.731, 95% CI 1.294 2.316; Model 3: OR=2.287, 95% CI 1.633 3.205; Model 4: OR=2.016, 95% CI 1.390 2.922) after the adjustment. The data of 5-year follow-up showed that the annual incidence of TNs was significantly higher in individuals with persistent H. pylori infection than non-infected counterparts (all p＜0.05). Conclusions: H. pylori is an independent risk factor for TNs in the adults of Northwest China.